Sverre Røiseland speaks about the Olympics Milano Cortina 2026 - Sattlecker, G. (Journal of Biathlon Coaching, 2025)
In this interview, Sverre Røiseland shares his experiences as a biathlon coach in Germany, highlighting cultural and coaching differences between Germany and Norway. He explains how he manages a female team with both young athletes and experienced stars like Franziska Preuss. Sverre covers key topics such as training organization, media engagement, and Olympic preparation, stressing the importance of team health and mental focus. He also reflects on how integrating new coaching approaches within the structured German system helps foster a supportive environment aimed at success in major competitions.